The use of Artificial Intelligence for Diagnosing Retinopathy of Prematurity – A Systematic Review - Pertiwi, Adinda Mulya; Yulia, Dian Estu; Lestari, Yeni Dwi (Indonesian Vitreoretinal Society, 2025)
Purpose: Retinopathy of prematurity (ROP) is a vaso-proliferative disease of the retina associated with prematurity and is well known to be the leading cause of childhood blindness worldwide. Given the prevalence of ROP and the increasing demand for efficient screening solutions, this systematic review aims to update the current development of Artificial Intelligence (AI) technologies for ROP diagnosis and screening, considering the appropriate AI types that align with the specific needs and workloads of ROP screening programs. Methods: We performed a systematic literature review of the English online literature databases by applying a general search strategy on April 20, 2024. Search phrases included multiple variants of terms including